Formative Evaluation of a Pilot Afterschool Physical Activity–Based Positive Youth Development Program. Issue 2 (March 2019) - Riciputi, Shaina; Boyer, Paige; McDonough, Meghan H.; Snyder, Frank J.
4-H PALS is an afterschool positive youth development program for pre- and early adolescents delivered within the 4-H platform and designed to use physical activity to promote character development. The conceptual framework for this program, informed by the theory of triadic influence, prioritizes the social environment created during physical activities to promote adaptive outcomes. Given the novelty of the 4-H PALS curriculum, it is important to outline program components and identify both strengths and challenges to be addressed. Thus, this study aimed to document, describe, and conduct a formative evaluation of 4-H PALS. Major themes were identified across leader and participant interviews, program observations, lesson planning notes, attendance records, and intervention team feedback using inductive analysis methods. Three key areas of evaluation were identified: curriculum implementation fidelity, participant engagement with the curriculum and context, and the social environment. The program was successful in creating an affirmative, engaging environment fostering positive self-perceptions and social outcomes for participants. Challenges with logistical and conceptual implementation of the curriculum's character development concepts were identified. This evaluation will inform program refinements, with the goal of preparing the program for an efficacy study examining outcomes among participating youth.